Neuroleptic malignant syndrome as part of an akinetic crisis associated with sepsis in a patient with Lewy body disease. Issue 2 (28th February 2019) - Manabe, Saki; Yanagi, Hidetaka; Ozawa, Hideki; Takagi, Atsushi
Abstract : A 65-year-old Japanese woman with Parkinson's disease, later diagnosed with Lewy body disease, presented with a 2-day history of systemic tremors. She also had fever without rigidity or creatine kinase (CK) elevation. She was diagnosed with sepsis caused by pyelonephritis with acute kidney injury and parkinsonism exacerbation. Although antibiotic and fluid therapy improved her pyuria and renal function, her fever and tremors persisted. On the fourth day, her symptoms worsened and resulted in cardiopulmonary arrest; however, quick resuscitation allowed the return of spontaneous circulation. Simultaneously, hyperthermia, altered consciousness, extrapyramidal symptoms, dysautonomia and CK elevation were noted. Thus, dantrolene administration was initiated with a tentative diagnosis of neuroleptic malignant syndrome (NMS). This caused her fever to subside, and her symptoms gradually improved. It was difficult to distinguish between parkinsonism exacerbation associated with sepsis and NMS. Physicians should consider NMS early on, even if the patient does not fulfil the diagnostic criteria.